The Effect of Health Education on Balanced Nutrition in Preventing Stunting in Toddlers on Mother's Knowledge in the Work Area of Pagurawan Health Center, Batu Bara Regency in 2021 - Kristina Kristina (Institute of Computer Science (IOCS), 2021)
Stunting is a health problem that is the focus of the government's health development program in 2015-2020 in addition to reducing maternal and under-five mortality rates, controlling infectious diseases and controlling non-communicable diseases. This study aims to determine whether there is an effect of health education on balanced nutrition in preventing stunting in toddlers on mother's knowledge in the working area of ​​the Pagurawan Public Health Center in Batubara Regency in 2021. This research is a quasi-experimental study with a one-group pretest-posttest design approach. This research has been carried out from September 2021 to October 2021. Sampling using accidental sampling with a total sample of 48 mothers who have toddlers aged 1-5 years. The results showed that the results of the Paired Sample-Test test obtained a p-value of -0.001 < =0.05 then H0 was rejected, meaning that simultaneously there was the effect of Health Education on balanced nutrition in preventing stunting in toddlers on mother's knowledge in the work area of ​​the Pagurawan Public Health Center, Batubara Regency. year 2021. Suggestions in this study in the Working Area of ​​the Pagurawan Health Center in Batu Bara Regency play an active role in seeking information, especially for midwives in the Work Area of ​​the Pagurawan Health Center in Batu Bara so that mothers can gain knowledge about balanced nutrition in toddlers for stunting prevention. meaning that simultaneously there was the effect of Health Education on balanced nutrition in preventing stunting in toddlers on mother's knowledge in the work area of ​​the Pagurawan Public Health Center, Batubara Regency. year 2021. Suggestions in this study in the Working Area of ​​the Pagurawan Health Center in Batu Bara Regency play an active role in seeking information, especially for midwives in the Work Area of ​​the Pagurawan Health Center in Batu Bara so that mothers can gain knowledge about balanced nutrition in toddlers for stunting prevention. meaning that simultaneously there was the effect of Health Education on balanced nutrition in preventing stunting in toddlers on mother's knowledge in the work area of ​​the Pagurawan Public Health Center, Batubara Regency. year 2021. Suggestions in this study in the Working Area of ​​the Pagurawan Health Center in Batu Bara Regency play an active role in seeking information, especially for midwives in the Work Area of ​​the Pagurawan Health Center in Batu Bara so that mothers can gain knowledge about balanced nutrition in toddlers for stunting prevention.